ANALYSIS OF POPULATION WELFARE AS A SUPPORTER OF SUSTAINABLE DEVELOPMENT IN BANTEN PROVINCE - Riny Handayani (INJOSEDU: International Journal of Social and Education, 2025)
One indicator of development success can be seen from the Human Development Index (HDI) which is calculated based on 3 aspects, namely Education, Health and Community Purchasing Power. The biggest hope of development planning is the welfare of the population. Therefore, in determining policies in the form of priority programs and activities in development planning through population development mapping analysis, it is very important to know population dynamics by utilizing population data. Population development information is strategic information and is very much needed for planning population-oriented and sustainable development policies. Population-oriented development means development that is adapted to the potential and conditions of the existing population. This research uses a mixed approach, namely the use of qualitative and quantitative approaches (Blending Quantitative and Qualitative Research) Bryman, 2014. The percentage of population morbidity in Banten Province in 2020 - 2022 continues to experience a downward trend, reaching around 11.38% more low compared to the national level, namely 13.36%. The region with the highest UHH in 2022 is still South Tangerang City, namely 72.78 years, and the lowest is Serang Regency, namely 65.18 years. All districts/cities in Banten Province experienced an increase in terms of population expenditure per capita. The highest value of population expenditure per capita is South Tangerang City, while the lowest is Pandeglang Regency. The poverty rate in Banten Province (6.16 percent) is quite low compared to the national average, namely 9.54 percent. However, the condition of poverty in Banten Province must be addressed immediately because if not, this will become a quite serious threat to Banten Province in the future.